Bone Scintigraphy of Vertebral Fractures With a Whole-Body CZT Camera in a PET-Like Utilization - Bahloul, Achraf; Verger, Antoine; Blum, Alain; Chawki, Mohammad Bilal; Perrin, Mathieu; Melki, Saifeddine; Karcher, Gilles; Marie, Pierre-Yves; Imbert, Laetitia (Frontiers in Nuclear Medicine, 2021)
An image display with an SUV scale is recommended for analyzing PET exams, thus requiring the reconstruction of accurate images for both SUV measurement and visual analysis. This study aimed to determine whether such images may also be obtained with a high-speed CZT SPECT/CT system, with a further application for the longitudinal monitoring of vertebral fractures. Materials and Methods. SPECT image reconstruction was optimized with an IEC phantom according to both image quality parameters and accuracy of measured activity. The optimized reconstruction process was applied to ≤ 15 min 99mTc-HDP SPECT spine recordings previously acquired from 25 patients (74±12 years old) at both early (1.3±1.1 months) and late (5.2±2.3 months) stages after an acute vertebral fracture. Results. A SPECT reconstruction with 32 equivalent iterations was selected based on the association of high detectability for spheres down to 0.6 mL in volume, with accurate measured activity, although the latter was affected by partial volume effect for spheres ≤ 5.8 mL. Coherent measurements were obtained on these high-quality SPECT images for the SUVmax from patients’ intact vertebrae, which were stable between 1st and 2nd SPECT recordings (for T1 vertebrae: 5.7±1.1 vs. 5.8±1.1, p=0.76), and from initially fractured vertebrae, which were dramatically higher on the 1st compared to the 2nd SPECT (21.0±8.5 vs. 11.2±4.2, p<0.001), whereas inverse changes in SUVmax were observed for newly compacted fractures identified on 2nd SPECT (74.4±2.0 vs. 21.8±10.3, p=0.002). Finally, an image display with an SUV scale was shown to be advantageous for highlighting areas with >7.5 SUV, a level reached by 98% of vertebral fractures of <7-months and 4% of reference intact vertebrae. Conclusion. Bone scintigraphy of vertebral fractures may be obtained with this CZT-SPECT/CT system with fast 3D-acquisitions and high-quality images displayed with a reliable SUV scale, approaching what is achieved and recommended for PET imaging.